The Social Lives of Married Women : Peer Effects in Female Autonomy and Investments in Children - Kandpal, Eeshani (World Bank, Washington, DC, 2019)
In patriarchal societies, sticky norms affect married women's social circles, their autonomy, and the outcomes of intra-household bargaining. This paper uses primary data on women's social networks in Uttarakhand, India; the modal woman has only three friends, and over 80 percent do not have any friends of another caste. This paper examines the effect of a shock to friends' empowerment on a woman's autonomy, specifically physical mobility, access to social safety nets, and employment outside the household; perceived social norms; and an outcome of household bargaining: investments in her children. The analysis instruments for endogenous network formation using a woman's age and her caste network in the village. The key peer effect is the impact of having a friend who received an empowerment shock on a woman who did not receive that shock. The results show significant peer effects on only a few of the examined measures of women's autonomy. In contrast, peer effects exist on all considered outcomes of a daughters’ diet and time spent on chores. The findings suggest a large decay rate between effects on own empowerment and peer effects. Interventions targeting child welfare through women's empowerment may generate second-order effects on intra-household decision-making, albeit with substantial decay rates, and thus benefit from targeted rather than randomized rollout. In contract, interventions on gender roles and women's autonomy may be limited by the stickiness of social norms.